A model of speech production ascending to L.S. Vygotsky's School: Principles and verification - T.V. Akhutina (Ученые записки Казанского университета: Серия Гуманитарные науки)
In this article, the development and verification of the A.A. Leontiev–T.V. Akhutina model of speech production based on L.S. Vygotsky's ideas is discussed. The conceptual and experimental background of L.S. Vygotsky's theory of speech thinking is analyzed. The ideas of this theory opened the way to a prudent approach to understanding the controversy in psycholinguistics of the 1960s–1970s (works by A.A. Leontiev), A.R. Luria's findings in aphasiology, and the results of T.V. Akhutina's research in the field of agrammatism. This determined, in many ways, the specifics of the general framework of the model. The major psycholinguistic concepts elaborated in the 1970s are considered, i.e., those introduced by Ch. Fillmore, C. Lee and S. Thompson, J. Bruner and E. Bates, all shedding light on the syntactic operations of the model. The verification of these ideas in the studies describing syntax in children's speech, “pidgin” and creole languages, etc. is carried out. The recent observations of the problem being studied at the intersection of linguistics, psychology, and neurosciences are summarized. Particular attention is paid to R. Jackendoff and E. Wittenberg's review of “linear” languages, as well as to the experimental studies by R. Tomlin, A. Myachikov, A. Konopka that fit with the A.A. Leontiev–T.V. Akhutina model of speech production. The conclusion is made about the high explanatory potential of L.S. Vygotsky's ideas and the model based on them.